Recent advances in omic technologies for meat quality management. (November 2015) - Picard, B.; Lebret, B.; Cassar-Malek, I.; Liaubet, L.; Berri, C.; Le Bihan-Duval, E.; Hocquette, J.F.; Renand, G.
Abstract: The knowledge of the molecular organization of living organisms evolved considerably during the last years. The methodologies associated also progressed with the development of the high-throughput sequencing (SNP array, RNAseq, etc.) and of genomic tools allowing the simultaneous analysis of hundreds or thousands of genes, proteins or metabolites. In farm animals, some proteins, mRNAs or metabolites whose abundance has been associated with meat quality traits have been detected in pig, cattle, chicken. They constitute biomarkers for the assessment and prediction of qualities of interest in each species, with potential biomarkers across species. The ongoing development of rapid methods will allow their use for decision-making and management tools in slaughterhouses, to better allocate carcasses or cuts to the appropriate markets. Besides, their application on living animals will help to improve genetic selection and to adapt a breeding system to fulfill expected quality level. The ultimate goal is to propose effective molecular tools for the management of product quality in meat production chains. Highlights: Genomics provided new knowledge in meat species. Genomics allowed the identification of biomarkers of meat quality traits in beef, pork and poultry. New genomic tools should be used to predict meat quality traits.